The relationship between immunocompetence, parasite load and reproductive effort in the highveld mole-rat (Cryptomys hottentotus pretoriae) Roberts 1913. - Bennett, Nigel Charles (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.